Role of Accounting Zakat as a Support Function in Supply Chain Management: A Resurrection of the Islamic Economy - Doktoralina, Caturida Meiwanto; Bahari, Zakaria; Ismail, Nor Asmat; Herliansyah, Yudhi; Putri, Gina Permana (International Journal of Supply Chain Management, 2018)
Within the increasingly competitive markets and the rapid changes in business all over the world today, it has become imperative for organizations to reconsider supply chain management (SCM) strategies due to the fact that the same SCM strategy may not appropriate for all organizations. The success of a strategy in a given business does not necessarily mean that it will be successful in others. Therefore, it is always important to explore new and non-traditional strategies for SCM. In the face of this argument, the present study argues for the effective role of Zakat as a support function in SCM. The focus is to illustrate how Zakat can perform an important job in SCM practices from an Islamic economic perspective. Experiences from governmental and non-governmental Zakat organizations in Indonesia are investigated with the purpose of indicating how Zakat, as an Islamic economic principle, can be usefully used in SCM practices. This study finally concludes that Zakat can play an effective role as a successful strategy in SCM. The findings of the study reflect the need to reconsider the concept and functions of different Islamic concepts including Zakat in order to keep up with the changes and challenges of modern societies. The implications of the study can be useful in SCM practices for both Islamic and conventional economies. They can also be considered in countries where Muslims are a minority.